Development of Video-Assisted Mathematics Learning Materials Using the SAVI Model to Enhance Mathematical Representation Skills - Ahyu Rahmah; Elita Zusti Djamaan; Ahmad Fauzan; Yulyanti Harisman (Universitas Pendidikan Ganesha, 2025)
Mathematical representation is an essential skill in the Merdeka Curriculum; however, assessment results indicate that this ability still needs improvement. The purpose of this study was to develop learning tools (Teaching Module, Student Worksheet (LKPD), and Learning Video) that can enhance students’ mathematical representation ability. This study applied the Plomp development model, which consists of three stages: preliminary research, prototyping, and assessment. The research subjects included experts for validation, three students with different ability levels for the one-to-one trial, six students for the small group trial, and one full class for the field test. Data were collected through interviews, observations, literature review, validation sheets, questionnaires, and interviews with both students and experts. Data analysis was carried out using quantitative techniques for validation and effectiveness, combined with qualitative interpretation and descriptive statistics. The results showed that the developed learning tools were declared valid by experts with validity scores of 4.10, 4.03, 4.11, 4.13, and 4.88, respectively. The tools were also highly practical, with practicality scores of 94.67% from teachers and 93.73% from students, and effective in improving mathematical representation skills with an average test mastery of 73%. Based on these results, it can be concluded that mathematics learning tools assisted by video using the SAVI model are valid, practical, and effective. The implication is that these findings contribute to the development of innovative mathematics learning that supports the enhancement of students’ mathematical representation skills.